2017
DOI: 10.4103/sni.sni_450_16
|View full text |Cite
|
Sign up to set email alerts
|

Primary pituitary neuroendocrine tumor: Case report and literature review

Abstract: Background:Neuroendocrine tumors (NET) originate from the diffuse neuroendocrine system. These can arise in almost every organ of the body, although they are most commonly found in the gastrointestinal tract and respiratory system. The skull base and sellar region are extremely rare sites for neuroendocrine carcinoma. Consequently, in this case, both diagnosis and definition of surgical goals, as well as further treatment strategies were challenging.Case Description:A 65-year-old woman was admitted to our Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…Pituitary tumors are considered as one of the most common intracranial neoplasms of the central nervous system (1,2). Although the majority of pituitary adenomas are benign tumors, ~25% of the tumors invade areas of the intracranial region (3).…”
Section: Introductionmentioning
confidence: 99%
“…Pituitary tumors are considered as one of the most common intracranial neoplasms of the central nervous system (1,2). Although the majority of pituitary adenomas are benign tumors, ~25% of the tumors invade areas of the intracranial region (3).…”
Section: Introductionmentioning
confidence: 99%
“…4) Primary intracranial NETs are extremely rare entities, and to date, only 12 cases have been reported in the literature. 1,[4][5][6][7][8][9][10][11][12][13] Most were located in the skull base and sellar regions, except for one case each in the third ventricle, 1) frontal convexity, 6) parietal lobe, 9) and cerebellum. 13) Based on the pathological findings of the present case, we consider that the differential diagnosis of NETs should include esthesioneuroblastoma and ectopic sparsely granulated corticotroph adenoma (SGCA).…”
Section: Discussionmentioning
confidence: 99%
“…Esthesioneuroblastoma usually comprises neuroblasts with uniform circular nuclei and longitudinal cerebromedullary tubes in the dendrites, but NETs originate from the epithelium and lack neural features. [6][7][8]10,11) On electron microscopy, verification of the presence of intracytoplasmic neuroendocrine granules is highly valuable for the differential diagnosis of NETs. 10) Intraoperative findings in this case indicated that the sellar dura was preserved and there was no continuity between the tumor and the pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transsphenoidal surgery is usually considered as the first-choice therapy for most patients with pituitary tumors, which is an effective and safe treatment (2). Comprehensive therapy is gradually important among endocrinologists, ophthalmologists, and radiologists (3). Thus, it is helpful to clarify the pathogenesis and progression of pituitary tumors.…”
Section: Introductionmentioning
confidence: 99%